2021
DOI: 10.1039/d1sc01007g
|View full text |Cite
|
Sign up to set email alerts
|

Actinide tetra-N-heterocyclic carbene ‘sandwiches’

Abstract: Highly-symmetrical, thorium and uranium octakis-carbene ‘sandwich’ complexes have been prepared by ‘sandwiching’ the An(iv) cations between two anionic macrocyclic tetra-NHC ligands, one with sixteen atoms and the other with eighteen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…From a theoretical viewpoint, an An complex is likely to exhibit a complicated multiconfigurational ground state (GS) because of the open 5f shell. Although Kohn–Sham DFT rests on a single Slater determinant, it is often the method of choice for geometry optimizations and chemical bonding analyses, , thermodynamic properties, ,, and even magnetic properties ,, of medium size to large actinide systems. Multiconfigurational wavefunction-based methods, such as complete active-space (CAS) self-consistent field (SCF) approaches, are well-suited for An chemistry research, especially for susceptibility and NMR calculations, magnetic circular dichroism (MCD), or other areas that require accurate treatment of the unpaired electrons and static correlation. CAS-level calculations are usually conducted based on crystal structure geometries, if available, or optimized DFT geometries.…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical viewpoint, an An complex is likely to exhibit a complicated multiconfigurational ground state (GS) because of the open 5f shell. Although Kohn–Sham DFT rests on a single Slater determinant, it is often the method of choice for geometry optimizations and chemical bonding analyses, , thermodynamic properties, ,, and even magnetic properties ,, of medium size to large actinide systems. Multiconfigurational wavefunction-based methods, such as complete active-space (CAS) self-consistent field (SCF) approaches, are well-suited for An chemistry research, especially for susceptibility and NMR calculations, magnetic circular dichroism (MCD), or other areas that require accurate treatment of the unpaired electrons and static correlation. CAS-level calculations are usually conducted based on crystal structure geometries, if available, or optimized DFT geometries.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has allowed the isolation of a number of interesting metal complexes 46 49 of the early transition metals, 50 71 the lanthanides, 72 80 and the actinides. 81 86 …”
Section: Introductionmentioning
confidence: 99%
“…However, this weak bond may be enhanced by harnessing anionic linkers. This strategy has allowed the isolation of a number of interesting metal complexes of the early transition metals, the lanthanides, and the actinides. …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that a direct deprotonation approach, as opposed to transmetalation, was required to synthesize metal complexes of H 4 ( BMe 2 ,Me TC H )­(Br) 2 . Unlike examples with transition metals, our attempts to form the target lanthanide complexes with n BuLi, LiN i Pr 2 , or KN i Pr 2 as the base were unsuccessful. , The deprotonation of H 4 ( BMe 2 ,Me TC H )­(Br) 2 in dimethoxyethane with NaN­(SiMe 3 ) 2 (NaHMDS) at −35 °C, followed by the addition of anhydrous LuBr 3 , with subsequent heating at 50 °C for 24 h yielded ( BMe 2 ,Me TC H )­Lu­(HMDS) ( 1 ) in 22% isolated yield after recrystallization from pentane, as shown in Scheme (top). This synthetic approach is similar to our synthesis of actinide “sandwich” complexes such as ( BMe 2 ,Me TC H ) 2 U . This reaction was also successful with other solvents such as pyridine, CH 3 CN, and t BuCN, albeit with reduced yields.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our group has previously reported the synthesis of dianionic tetra-NHC macrocycles for transition metals such as iron and chromium and very recently actinides, including uranium and thorium . Thus, we thought that these anionic tetra-NHC macrocycles would be suitable candidates to ligate to lanthanides.…”
Section: Introductionmentioning
confidence: 99%